2023
DOI: 10.3390/ijms241411403
|View full text |Cite
|
Sign up to set email alerts
|

HER2-Positive Gastric Cancer: The Role of Immunotherapy and Novel Therapeutic Strategies

Abstract: Gastric cancer is an aggressive disease with increasing global incidence in recent years. Human epidermal growth receptor 2 (HER2) is overexpressed in approximately 10–20% of gastric cancers. The implementation of targeted therapy against HER2 as part of the standard of care treatment in metastatic disease has improved the prognosis of this subset of patients. However, gastric cancer still has high mortality rates and urgently requires new treatment strategies. The combination of immunotherapy with HER2-target… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 138 publications
0
3
0
Order By: Relevance
“…In our cohort, seven out of nine (77.8%) HER2-positive tumors were also PD-L1 CPS ≥ 1. Previous studies showed higher and lower rates of PD-L1 CPS ≥ 1 in HER2-positive tumors, which can be related to population heterogeneity or differences in biomarker evaluation, and should be further explored [ 30 , 31 ]. Interestingly, previously proposed molecular classification systems of gastric cancer do not place HER2 and PD-L1 enrichment within the same tumor subtypes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, seven out of nine (77.8%) HER2-positive tumors were also PD-L1 CPS ≥ 1. Previous studies showed higher and lower rates of PD-L1 CPS ≥ 1 in HER2-positive tumors, which can be related to population heterogeneity or differences in biomarker evaluation, and should be further explored [ 30 , 31 ]. Interestingly, previously proposed molecular classification systems of gastric cancer do not place HER2 and PD-L1 enrichment within the same tumor subtypes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, HER2 alteration and, more recently, PD-L1 expression are the only predictive biomarkers of response that can be useful to a clinician in the first-line decision-making process. Based on a strong preclinical rationale, combining immune-checkpoint inhibitors with HER2-directed agents has catalysed the interest of clinical research in the treatment of HER2-positive GEA [88]. The positive results of KEYNOTE-811 have changed the standard of care for HER2-positive/PDL1-positive advanced GEA.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies established that HER2 controls the abnormal expression of PD-L1 in the stomach and the combination of anti-HER2 and anti-PD-1 has proven synergistic anticancer effects in animal models ( 16 , 28 , 29 ). Further studies disclosed that dimerization of the HER2 receptor activates two major intracellular signaling pathways: the mitogen-activated protein kinase (MAPK) (Ras/Raf/MEK/ERK) and phosphatidylinositol 3′-kinase (PI3K)/Akt, inducing cell-cycle progression, proliferation and survival ( 30 32 ). PD-L1 is a dynamic marker that can be expressed constitutively (driven by endogenous oncogenic pathways) or in an inducible fashion (motivated by exogenous signals) ( 33 ).…”
Section: Discussionmentioning
confidence: 99%